Chemoselectivity in the Transannulaction of 1, 2, 3‐Thiadiazoles and Alk‐2‐enenitriles: Specific Synthesis of 3‐(Alk‐1‐enyl)isothiazoles. Issue 4 (24th January 2022) - Wu, Qiuyue; Chen, Ning; Xu, Jiaxi
Abstract: 1, 2, 3‐Thiadiazoles are precursors of thioacylcarbenes and thioketenes and show various reactions with unsaturated compounds. The rhodium‐catalyzed reactions of 1, 2, 3‐thiadiazoles and alk‐2‐enenitriles, including alkyl, aryl, and heteroaryl acrylonitriles, have been investigated, showing chemospecific reactivity to generate 3‐vinylisothiazole derivatives via the (3+2) transannulation between the cyano group of alk‐2‐enenitriles and generated thioacylcarbenes. ( Z )‐Cinnamonitriles are less active than ( E )‐cinnamonitriles due to the strong coordination of the ( Z )‐C=C bond and the Rh catalyst. The current reaction provides a method for the synthesis of 3‐vinylisothiazole derivatives. Abstract : The rhodium‐catalyzed reactions of 1, 2, 3‐thiadiazoles and alk‐2‐enenitriles, including alkyl, aryl, and heteroaryl acrylonitriles, have been investigated, showing chemospecific reactivity to generate 3‐vinylisothiazole derivatives via the (2+3) transannulation between the cyano group of alk‐2‐enenitriles and generated thioacylcarbenes. ( Z )‐Cinnamonitriles are less active than ( E )‐cinnamonitriles due to the strong coordination of the ( Z )‐C=C bond and the Rh catalyst.